(untitled) (Baghdad Science Journal, 2019)
The experiment was conducted in two stages: first stage: determination of the most effective dose of Cyperus rotundus tubers aquatic extract in male rats for 5 days, which was concentrated as (200 mg/kg body weight). The second stage was designed to observe and test the protective effects of C. rotundus tubers aquatic extract in the liver and kidney functions of male rats exposed to cadmium chloride poisoning (5 mg/kg bw) for 30 days. The animals were divided into (4) groups within each group (5) animals weighted (200-220g). The results of oral dose of cadmium chloride showed a significant increase of (P˂0.05) in the activity of both enzymes Alanine aminotransferase (ALT), Aspartate aminotransferase (AST), Alkaline phosphatase (ALP), glucose, urea, uric acid, creatinine, malondialdehyde (MDA) and peroxynitrite (ONOO-). And a significant decrease (P˂0.05) in the values ​​of total protein, albumin, globulin and glutathione (GSH) compared with the control group. The oral dosage of the C. rotundus tubers aquatic extract resulted in a significant increase in GSH. The values ​​of each were not significantly different ALT, AST, ALP, Glucose, urea, uric acid, creatinine, total protein, albumin, globulin, MDA and peroxy nitrite Compare with control group. The results of the oral dosage with (C. rotundus tubers aquatic extract + cadmium chloride) showed a positive effect on these values ​​compared with the control group and cadmium chloride. It is concluded that the C. rotundus tubers aquatic extract has protective effects and reduces the effects that cadmium chloride can cause in rats liver and kidney functions through its antioxidant activity and removal of free radicals.